Clinical value of ELISA assays for IgM and IgG rheumatoid factors. - Stone, R (1987)
The clinical value of enzyme linked immunosorbent assays (ELISA) assays for IgM and IgG rheumatoid factors was assessed in a series of studies using rabbit IgG as antigen. The tests were reproducible with intra-assay coefficients of variation of 6% and could be simply and rapidly performed. Normal ranges were established using 106 sera from healthy controls. In a cross sectional study of 208 rheumatoid patients these assays were compared with the Rose-Waaler and laser nephelometric assessments of rheumatoid factor. In some patients there were discrepancies between rheumatoid factor positivity determined by one method or another. IgM ELISA and Rose-Waaler titres showed a significant correlation (r = +0.58; p less than 0.001), but there was a low correlation between IgM and IgG ELISA (r = +0.27; p less than 0.001). There was no evidence to show that the measurement of IgM or IgG rheumatoid factor gave significantly more clinical information than traditional tests such as the Rose-Waaler or latex agglutination tests.